INSTRUCTIONAL TEXTS AND THEIR FUNCTIONS - Master: Toshkulova M. M. (The Conference Hub, 2025)
This article is about functions and descriptions of instructional texts in English language.
Keywords: instruction, description, preparation, perform, process, indecations.